1965
DOI: 10.1177/00220345650440031201
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Studies of the Natural History of Caries. I. Eruption Patterns of the Permanent Teeth

Abstract: Since the recognition of the potential of fluorides as caries preventatives, the interest of many dental epidemiologists has shifted from descriptive to experimental studies of oral disease, resulting in unprecedented advances in the control of caries and its sequelae. Judging from the proportion of effort in this direction, there has been a tendency to overlook the fact that the descriptive epidemiology of caries remains vague in several important, if undramatic, areas. Among these can be cited the equivocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
2
3

Year Published

1977
1977
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 13 publications
8
68
2
3
Order By: Relevance
“…This result suggested that, to improve dental health in this high-risk population, we should take protective measures to promote healthy dental hygiene behavior for children and adolescents between 1 and 18 yrs of age, because there is no "threshold age" after which a caries-free person's risk of caries onset is significantly reduced. The continuous decline of caries onset risk with age differs from findings reported by the classic dental study by Carlos and Gittelsohn (1965) and later supported by Harkanen et al (2002), showing that the "caries attack risk" of permanent teeth peaks 2 to 4 yrs after tooth eruption and declines thereafter. The difference between our study results and earlier ones stems from our exclusion of individuals with caries at enrollment; thus, older participants had already passed the peak of caries attack risk, while young participants experienced higher caries attack risk at the second visit.…”
Section: Discussioncontrasting
confidence: 65%
“…This result suggested that, to improve dental health in this high-risk population, we should take protective measures to promote healthy dental hygiene behavior for children and adolescents between 1 and 18 yrs of age, because there is no "threshold age" after which a caries-free person's risk of caries onset is significantly reduced. The continuous decline of caries onset risk with age differs from findings reported by the classic dental study by Carlos and Gittelsohn (1965) and later supported by Harkanen et al (2002), showing that the "caries attack risk" of permanent teeth peaks 2 to 4 yrs after tooth eruption and declines thereafter. The difference between our study results and earlier ones stems from our exclusion of individuals with caries at enrollment; thus, older participants had already passed the peak of caries attack risk, while young participants experienced higher caries attack risk at the second visit.…”
Section: Discussioncontrasting
confidence: 65%
“…This effect of dental immaturity has been known for many years from longitudinal studies of the natural history of caries [Carlos and Gittelsohn, 1965]. Children with recently erupted or erupting teeth have the greatest potential to show a benefit with an effective caries-preventive agent (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Caries risk is particularly high in the young during the early posteruptive years of the primary and permanent dentition (Carlos & Gittelsohn 1965). Early childhood caries may arise due to incorrect feeding habits (increased sugar exposure during weaning, bottle feeding or prolonged nocturnal breast-feeding) (Avila et al 2015, Tham et al 2015.…”
Section: Are Periodontal Diseases Related To Diet? If So What Are Thementioning
confidence: 99%